UNFOLDING MORAL IDENTITY AMONG ADOLESCENTS: ITS CULTIVATION WITHIN THE EDUCATION REALM - Anis Shaari; Berlian Nur Morat, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
While there is growing global and national interest in fostering moral identity (MI) as a foundation for moral behaviour, the existing belief among Malaysian society members places a stronger emphasis on grade attainments, presenting opportunities to further enhance moral development. This may be due to the long-practised exam-centric education in the country. As the current education system is promoting a more balanced intellectual-character aspiration, this conceptual paper explores the MI cultivation among adolescents within the Malaysian education context, emphasising its significance alongside academic achievement. Drawing from both theoretical and empirical research, the paper advocates for a balanced educational approach that nurtures both intellect and character through the role of teacher and parental care in adolescents’ MI formation. The paper concludes with a call for educators to prioritise moral identity development to address the ongoing moral decline and meet Malaysia’s educational aspirations.